Analysis of Hellenistic glass from Satricum - Higgons, Melinda (2017)
This dissertation is presented for an MSc (by Research) in Archaeological Materials. It covers a variety of topics relating to the ultimate goal: provenancing the samples of eleven glass artifacts found in a votive deposit at Satricum, Italy. This paper introduces the reader to the world of glass as a material, both from a cultural and scientific view. The history of the site of Satricum and the surrounding areas is explored in order to provide a background on the possible origins of the artifacts found there. A history of glass from its invention is also covered to explain the importance of glass artifacts and where they may have been made during the relevant time period. Eleven samples from glass fragments found at Satricum in Italy were analyzed. Dating from the third to second centuries BCE, the samples were all found in a votive deposit at the temple site during the excavations by the Satricum Project, which are currently run by the University of Amsterdam. Using the chemical analysis of the samples, by electron microprobe analysis run by Dr. Andy Tindle at the Open University, along with historical references and other evidence, probable provenances of the artifacts are suggested. Since there is a rather significant lack of information and evidence regarding the provenances of ancient glass, possible hypotheses instead of definite conclusions are discussed.